2011
DOI: 10.1021/am200810x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive SERS Detection of As3+ Ions in Aqueous Media using Glutathione Functionalized Silver Nanoparticles

Abstract: A highly sensitive surface-enhanced Raman scattering (SERS) platform for the selective trace analysis of As3+ ions was reported based on glutathione (GSH)/4-mercaptopyridine (4-MPY)-modified silver nanoparticles (AgNPs). Here, GSH conjugated on the surface of AgNPs for specifical binding with As3+ ions in aqueous solution through As–O linkage and 4-MPY was used as a Raman reporter. When As3+ ions were added to the system, the binding of As3+ with GSH resulted in the aggregation of AgNPs, and excellent Raman si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
136
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(138 citation statements)
references
References 43 publications
0
136
0
2
Order By: Relevance
“…6 The detection task is mainly carried out using analytical instruments such as atomic emission 7 or absorption spectroscopy, 8 ICP-MS, 9 or surface enhanced Raman scattering. 10,11 Developing cost-effective biosensors might provide a complementary solution. 12 For example, genetically engineered bacterial cells, 13 and enzyme inhibition assays were developed to detect arsenic.…”
mentioning
confidence: 99%
“…6 The detection task is mainly carried out using analytical instruments such as atomic emission 7 or absorption spectroscopy, 8 ICP-MS, 9 or surface enhanced Raman scattering. 10,11 Developing cost-effective biosensors might provide a complementary solution. 12 For example, genetically engineered bacterial cells, 13 and enzyme inhibition assays were developed to detect arsenic.…”
mentioning
confidence: 99%
“…For this purpose, the nanoparticles such as core-shell-type nanoparticles including gold nanoshells, [99][100][101][102] nanocrescents, 103 and hollow gold nanospheres [104][105][106][107] have been synthesized, and their applicability as effective SERS probes has been tested. 77,85 The different shape nanoparticles have potential to meet the requirements of the SERS measurement. More importantly, gold nanorods (GNRs) have been introduced as powerful imaging probes for biomedical and biological applications.…”
Section: Metal Nanocolloidsmentioning
confidence: 99%
“…21 Up to now, various AgNPs-based SERS applications have been reported. 16,[21][22][23][24] For example, Ren et al have reported the determination of mercury ions by a direct SERS technique based on the interaction between AgNPs and mercury ions. 21 Jiang et al have developed a AgNPs aggregates-based SERS substrate for sensitive detection of polycyclic aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…22 Our group has developed a highly sensitive SERS strategy for detection of arsenic ions by using glutathione functionalized AgNPs. 23 In general, SERS-based assay is conducted by two modes, i.e., via controlling distance between reporter and substrate, and based on aggregation. 24 However, to the best of our knowledge, there have been no examples based on anti-aggregation of AgNPs for SERS detection of proteases.…”
Section: Introductionmentioning
confidence: 99%